Increasing Cauliflower Yields through Fertigation - Majesta Esa Sofian; Anas Dinurrohman Susila (Journal of Tropical Crop Science, 2018)
Cauliflower is one the important vegetable crop in the tropics; the curd contains high fibres, potassium, carotene and vitamin C. However, the production and productivity of cauliflower in Indonesia has been low and cannot meet the demand, resulting in high importation of cauliflowers into Indonesia. Bogor Agricultural University has developed potential lowland cauliflower genotypes, BOB017 and BOB020, with higher productivity. In this study, we evaluated three fertigation methods on the growth, yield and economic returns of the two lowland cauliflower genotypes.  The experiment was arranged in a split-plot design with four replications. The main plot contained two cauliflower genotypes, BOB017 and BOB020. The subplot was three fertilizer application methods: through drip irrigation, soil drench, and drilled. The results showed that BOB020 had an earlier harvest time (60 days) compared to BOB017 (71 days). The soil drench fertigation method showed the highest curd weight (351.64 g), curd diameter (14.65 cm) and yield (12.39 t.ha-1) compared to the other two fertigation methods. The BOB017 genotype fertilized with soil drench method resulted in the highest B/C ratio (3.32). The study concluded that growing cauliflower using the soil drench method resulted in the optimum growth of cauliflower, high yield and net income.